Our singular strengths: meditations for librarians. Chicago: American Library Association, 1998. xv, 196 p. - Plaza, María Alejandra (2001)
Fil: Plaza, María Alejandra. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Departamento de Bibliotecología y Ciencia de la Información; Argentina